Angiogenesis stimulated by human kallikrein‐related peptidase 12 acting via a platelet‐derived growth factor B‐dependent paracrine pathway. Issue 2 (13th November 2013) - Kryza, Thomas; Achard, Carole; Parent, Christelle; Marchand‐Adam, Sylvain; Guillon‐Munos, Audrey; Iochmann, Sophie; Korkmaz, Brice; Respaud, Renaud; Courty, Yves; Heuzé‐Vourc'h, Nathalie
Abstract : KLK12, a kallikrein peptidase, is thought to take part in the control of angiogenesis. Our analysis of the secretome of endothelial cells (ECs) that had been treated with KLK12 showed that KLK12 converts the extracellular matrix‐ or membrane‐bound precursor of platelet‐derived growth factor B (PDGF‐B) into a soluble form. Both PDGF‐B and vascular endothelial growth factor A (VEGF‐A) take part in the induction of angiogenesis by KLK12 in a coculture model of angiogenesis that mimics endothelial tubule formation. We used a cellular approach to analyze the interplay between KLK12, PDGF‐B, and VEGF‐A and showed that release of PDGF‐B by KLK12 leads to the fibroblastmediated secretion of VEGF‐A. This then stimulates EC differentiation and the formation of capillary tube‐like structures. Thus, KLK12 favors the interaction of ECs and stromal cells. The released PDGF‐B acts as a paracrine factor that modulates VEGF‐A secretion by stromal cells, which ultimately leads to angiogenesis. Moreover, the genes encoding KLK12 and PDGFB are both expressed in ECs and up‐regulated in tumor cells kept under hypoxic conditions, which is consistent with the physiological involvement of KLK12 in PDGF‐B maturation.—Kryza, T., Achard, C., Parent, C., Marchand‐Adam, S., Guillon‐Munos, A., Iochmann, S., Korkmaz, B., Respaud, R., Courty, Y., Heuzé‐Vourc'h, N. Angiogenesis stimulated by human kallikrein‐related peptidase 12 acting via a platelet‐derived growth factor B‐dependent paracrine pathway. FASEB J. 28, 740–751 (2014). www.fasebj.org